A. C. Littleton's final thoughts on accounting : a collection of unpublished essays - Persson, Martin E. (Studies in the development of accounting thought ;, 2016)
Volume 20 of Studies in the Development of Accounting Thought (SDAT) is another fine example of informative and reflective analysis in the series. SDAT again provides readers with the firm historical foundations on which the profession is based, the historical antecedents of todays accounting institutions, the historical impact of accounting, as well as exploring the lives and works of pre-eminent individuals in the professions history. Studies in the Development of Accounting Thought focuses on bringing the past into today and using it to point towards the future.